ВДВ. Как выжить и победить в Афгане - Скрынников Михаил (Война. Чечня. Афган. Боевой опыт, 2010)
Экземпляры: ф.14 (20221220) / Инвентарный номер: 63057 / Цена: / Сис.шифр: 63.3(2)633-68 / Авт.знак: С 45 / ГРНТИ: 03.23.55 / ББК: 63.3(2)633-68